DEVELOPMENT OF COORDINATION SKILLS IN SENIOR AND PREPARATORY GROUP CHILDREN IN THE PROCESS OF PEDAGOGICAL EXPERIMENT (American Journal of Pedagogical and Educational Research, 2023)
The article presents the results of research work on teaching football elements in pre-school instituitons. Moreover, the results are compared gender-based: girls and boys in senior and preparatory groups of pre-school-institutions.